Direct antibiotic susceptibility testing of blood cultures of gram-negative bacilli using the Drug Susceptibility Testing Microfluidic (DSTM) device. Issue 6 (June 2020) - Mizoguchi, Miyuki; Matsumoto, Yoshimi; Saito, Ryoichi; Sato, Tomoaki; Moriya, Kyoji
Abstract: Proper treatment of bloodstream infections requires rapid, early determination of appropriate antibiotic agents, emphasizing the need for more rapid drug susceptibility testing. The Drug Susceptibility Testing Microfluidic (DSTM) device represents a novel method in which a small amount of bacterial suspension is injected into the microchip-like device and cultured for 3 h. However, it remains unknown whether the DSTM method can directly determine antibiotic susceptibilities from positive blood cultures. Here, we developed a new approach to directly assess drug susceptibility, using the DSTM method for positive blood cultures. We compare the utility and accuracy of DSTM with those of conventional susceptibility testing methods. Fifty positive blood cultures identified as gram-negative bacilli were used herein. The outcomes of drug susceptibility and resistance assays for positive blood cultures were compared to those of conventional susceptibility testing methods to evaluate their utility and accuracy. Method agreement rates between DSTM and standard methods often exceed 90%, suggesting a high positive correlation with conventional methods. Furthermore, our results show that a combination of multiple drugs in the DSTM device helps identify extended-spectrum β-lactamase (ESBL)- and AmpC-β-lactamase (AmpC-)-producing microorganisms. In conclusion, DSTM method enables effective drug susceptibility and resistance screening within 3 h from positive blood cultures and is suitable for the rapid and personalized determination of the antimicrobial regimen.